The Benefits of Collaborative Popular Music Songwriting: A Spectrum of Artist-Songwriter Involvement - Herbst, Jan-Peter; Williams, Katherine; Tolstad, Ingrid M.; Barber, Simon (Popular music and society, 2025)
This article explores the often overlooked role of professional songwriters in popular music, who occupy the spectrum between craftspeople and artists. Drawing on seventeen episodes of the Sodajerker podcast featuring songwriters who write for and with popular artists, we outline the role of professional songwriters in the popular music industry and how collaboration between songwriters and artists shapes and refines songs. On this basis, we propose a five-tiered spectrum of artist-songwriter involvement, ranging from independent songwriting by professionals without a specific artist brief to scenarios where artists are mostly self-sufficient but receive musical or psychological support from co-writers as needed.